Analysis of the Influence of Discipline and Work Performance on Job Satisfaction with Rewards as a Mediating Variable at PT. Cipta Karya Kendal, Central Java - Mukhlidin Mukhlidin; Garbada Boris Setyawan; Andi Fauziah Yahya (CV Edujavare Publishing, 2026)
This study aims to analyze the impact of work discipline and job performance on employee job satisfaction with appreciation as a mediating variable at PT Cipta Karya Kendal, Central Java. Disciplinary work and work performance are the main factors that influence the level of employee job satisfaction in an organization. However, the reward factor provided by the company also plays an important role as a mediator in the relationship. This research uses quantitative methods with a survey approach. Data were collected through questionnaires distributed to employees. Data analysis was carried out using Structural Equation Modeling (SEM) techniques to test the relationship between the variables studied. The results showed that work discipline has a positive and significant effect on job satisfaction. Job performance also has a positive influence on employee job satisfaction. In addition, rewards proved to be a mediating variable that strengthens the relationship between work discipline and job satisfaction, as well as between job performance and job satisfaction. With appropriate rewards, employees tend to be more motivated and feel valued, which ultimately increases their job satisfaction.